Adaptation and international climate policy. (18th March 2013) - Khan, Mizan R.; Roberts, J. Timmons
Abstract: Because of the failure of the world to agree an adequate regime to limit greenhouse gas emissions to a safe level, adaptation to climate change has risen rapidly in UN Framework Convention on Climate Change (UNFCCC) negotiations since 2007. We closely review the development of policies, institutions, and financing of adaptation in international agreements from 1992 to the present. We conclude that the way the treaty has been built—first as a mitigation regime with adaptation added on only later—has led to some profound problems for marrying the goals of economic development and building climate resilient societies. Particularly there are two problematic areas. First, following mitigation approaches, technical solutions are often the focus in adaptation projects, when social, political, and cultural problems lie at the roots of vulnerability and should be addressed directly. Second, early requirements that external funding would only come if the adaptation effort was clearly 'additional' to what would have been done without a changing climate have been extremely pernicious. By attempting to divide a development project from the 'additional' costs of adapting to climate change, the global policy has shaped adaptation efforts at the local level. To understand how we ended up with such quirky definitions of what counts as adaptation, we need to review the history of adaptation in the negotiated regimes. Finally, we trace the incomplete negotiations over who will pay for adaptation in developing countries, whether that funding will come as grants or loans, as private investment or public funds, and what say recipient countries will have. WIREs Clim Change 2013, 4:171–189. doi: 10.1002/wcc.212 This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Policy and Governance > International Policy Framework